2022
DOI: 10.3390/microorganisms10101964
|View full text |Cite
|
Sign up to set email alerts
|

Haemophilus influenzae Carriage among Healthy Children in Portugal, 2015–2019

Abstract: Haemophilus influenzae is an important cause of mucosal and invasive infections and a common colonizer of the upper respiratory tract. As there are no recent data on H. influenzae carriage in Portugal, we aimed to characterize carriage samples and investigate possible parallelisms with disease isolates. Between 2016–2019, 1524 nasopharyngeal samples were obtained from children (0–6 years) attending day-care. H. influenzae were serotyped and screened for β-lactamase production. Strains producing β-lactamase and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…A longitudinal study performed between 2015 and 2019 in Portuguese children up to 6 years old living in Lisbon showed an expected high rate of Hi nasopharyngeal colonization (84.3%), but Hib was detected only in 1 of 1524 samples (0.06%). 27 In the pre-vaccine period, serotype b carriage among Portuguese day-care center attendees was 3.8% suggesting that Hib vaccination nearly eliminated carriage of this serotype. 28 The serologic inquiry performed in Portugal in 2015-2016 showed a prevalence of protective antibodies titers (IgG > 1.0 μg/ mL) in 88.5% of the 2-4 years old, 86% of the 5-9 years old, 75.9% of the 10-14 years old and 79.4% of the 15 19 years old.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A longitudinal study performed between 2015 and 2019 in Portuguese children up to 6 years old living in Lisbon showed an expected high rate of Hi nasopharyngeal colonization (84.3%), but Hib was detected only in 1 of 1524 samples (0.06%). 27 In the pre-vaccine period, serotype b carriage among Portuguese day-care center attendees was 3.8% suggesting that Hib vaccination nearly eliminated carriage of this serotype. 28 The serologic inquiry performed in Portugal in 2015-2016 showed a prevalence of protective antibodies titers (IgG > 1.0 μg/ mL) in 88.5% of the 2-4 years old, 86% of the 5-9 years old, 75.9% of the 10-14 years old and 79.4% of the 15 19 years old.…”
Section: Discussionmentioning
confidence: 97%
“…A longitudinal study performed between 2015 and 2019 in Portuguese children up to 6 years old living in Lisbon showed an expected high rate of Hi nasopharyngeal colonization (84.3%), but Hib was detected only in 1 of 1524 samples (0.06%). 27 In the pre-vaccine period, serotype b carriage among Portuguese day-care center attendees was 3.8% suggesting that Hib vaccination nearly eliminated carriage of this serotype. 28…”
Section: Discussionmentioning
confidence: 97%
“…However, in their study, ampicillin was tested in the concentration range of 8 to 0.25 mg/L. For example, the authors Bajanca-Lavdo et al [36] tested 96 isolates of β-lactamase-producing strains of H. influenzae resistant to ampicillin and reported a lower MIC (4 mg/L) for tested strains. On the contrary, the authors Thiên-Trí Lâm et al [37] recorded a much higher MIC for tested isolates of H. influenzae.…”
Section: Discussionmentioning
confidence: 99%
“… 120 In Portugal, the β-lactamase positivity rate was 7.5% (96/1282). 12 In contrast, in France, the rate of β-lactamase positivity was as high as 27.1% (157/580) and 35.0% (208/595) for the BLNAR strains. 121 In Belgium, β-lactamase positivity was 23.8% (132/554) and 16.0% (15/94) in the carrier and invasive groups, respectively.…”
Section: Antibiotic Resistancementioning
confidence: 93%
“… 11 The total carrying rate of H. influenzae among children aged 0–6 in daycare was 84.1% (1282/1524), of which 96.7% (1240/1282) were NTHi. 12 A study in Shanghai, China found that all 51 isolates collected were NTHi, of which 5.9% (3/51) caused invasive infections, with ST103 (7.84%, 4/51) being the most common. 13 A multicenter study in Zhejiang, China, found that H. influenzae infections accounted for 18.5% (280/1514) and NTHi accounted for 93.6% (262/280).…”
Section: Epidemiologymentioning
confidence: 99%